HYBRIDS OF NAPPA CABBAGE FOR SOUTH ZONE IN AMUR OBLAST - V. F. Kirsanova; O. A. Kosytsina (Овощи России, 2017)
Napa cabbage is well spread in Japan, China, Korea, but it is not so well known in Far-Eastern regions of Russia. Since 2012 the collection of hybrid accessions has been evaluated at agrobiological station of Blagoveschensk State Pedagogical University located in western part of Blagoveschensk. Twenty local and foreign hybrids have been studied. As a result, seven highly-yielding accessions of different terms of maturity have been selected and included into State Register of Breeding Achievements of Russian Federation.  The  complex  assessment of  most  promising hybrids for uniform heads and excellent consumer’s characteristics has been performed  under the condition  of south zone of Amur oblast.